Does Perceived Value Moderate the Influence of Brand Image and Hedonic Lifestyle on Purchasing Decisions? Case: Starbucks Brand Coffee Consumer - Fauzi, Ahmad; Mutmainah, Isbandriyati; Mulia, Agus Prana (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
This study aimed to analyze the effect of brand image and hedonic lifestyle on purchasing decisions with perceived value as a moderating variable for Starbucks coffee consumers in Bogor City. The population of this study was all Starbucks Coffee consumers living in Bogor City, while the research sample was part of the population, which was collected using the convenience sampling method. Data was collected by distributing questionnaires online via the Google form to the respondents who were selected as samples. The dependent variable in this study is a purchasing decision, while the independent variables are brand image and hedonic lifestyle. The perceived value variable was chosen to be a variable that is thought to be able to moderate the effect of brand image and hedonic lifestyle on purchasing decisions. Moderated Regression Analysis method, with the help of SPSS 22 software. Using 127 respondents, the results of this study indicate that brand image and hedonic lifestyle partially have a positive and significant effect on purchasing decisions. The results with MRA show that the perceived value variable can moderate the effect of brand image and hedonic lifestyle on purchasing decisions of Starbucks Coffee brand coffee. The results of the F test simultaneously show that brand image and hedonic lifestyle have a positive and significant effect on purchasing decisions for Starbucks brand coffee.